About the Seyyid Gazi Zawiya and Its Annual Ceremonies (Journal of Alevism-Bektashism Studies, 2017)
The Seyyid Gazi zawiya is the leading religious center among the first religious centers formed in Anatolia. The zawiya and the name of Seyyid Gazi, sacred person to whom was dedicated the zawiya, have maintained the characteristic of being a religious center without an interruption since 13th century. The zawiye draws attention, especially in the Classical era, as the most important center of Kalandars in the Ottoman Empire. With the data from written sources, we can trace back ceremonies practiced in this zawiya to the first half of 15th century. In the Ottoman records, there are references to the ceremonies practiced every year in the autumn in the name of Seyyid Gazi. As we know, these ceremonies are also performed using some music instruments. In the same time, participants in ceremony or some of them whirl the “semah”. Certainly, ceremonies performed in this place were occasionally causing some discussions with Sunni Muslims who were generally accepted in the Ottoman world. On the one hand, the Ottoman administration granted some exemptions for the zawiya, founded in the name of Seyyid Gazi by accepting him as a sacred person, and for dervishes situated there, and even allowed dervishes to select their own sheikh. But on the other hand, it didn’t tolerate some rituals which were not acceptable by Sunni perception and made decision to prohibit these acts. Despite contradiction, it must be pointed out that the Ottoman central administration was taking the same approach in similar cases. In this short paper, we will try to open a window into the position of the zawiya in the Ottoman world by using documents and sources concerning these two perceptions, and to compare it with similar examples.